O Papel da transmissão de eletricidade inter e intrarregional em modelos de expansão e operação do sistema energético com forte penetração de fontes renováveis - Miranda, Raul Figueiredo Carvalho (2018)
According to the Intergovernmental Panel on Climate Change (IPCC), around 70-85% of global electricity in 2050 would have to be supplied by renewables. The avaialability of solar and wind resources is locational constrained and good resource spots are often located far away from where consumption will take place. In order to meet demand, the energy contained in solar and wind must be transformed into an energy carrier. to be transported. The transmission network is the most common system to do so, and therefore its planning is essential for a better use of solar and wind. Thus, the purpose of this study is to evaluate to what extent power grid representation impacts long-term energy planning modeling, and also how does it change the system’s operation profile. To do so, a TIMES model was used in the analysis of the Brazilian power system expansion. Also, a PLEXOS model was used to explore the interactions between different energy assets, particularly in the Northeast region of the country. Results show that energy prices significantly increase in restrictive scenarios as they represent that not always the least cost resource can be used. In the operation, transmission representation allows to properly assess the value of energy based on its generation location as well as the inherent costs of this process.